Detraining Decreases Hbmass of Triathletes - Eastwood, A.; Bourdon, P. C.; Snowden, K. R.; Gore, C. J. (International Journal of Sports Medicine, 2012)
Haemoglobin mass (Hbmass) determination using CO rebreathing may assist to detect illegal blood doping practices, however variations in Hbmass with periods of intensive training and detraining must be quantified. This study aimed to determine the effect of a 30-day period of detraining on Hbmass in ultra-endurance triathletes. 9 male recreational triathletes (29–44 years) participated in the study. Hbmass was assessed using CO rebreathing 30 days and 10 days before an ultra-endurance triathlon and after ~10, 20 and 30 days of detraining following the race. V˙O2max was assessed 10 days before the race and also after the 30-day detraining period, which consisted of an 87% reduction in training hours. After 30-days of detraining there was a 3.1% decrease in mean Hbmass from 868±99 to 840±94 g, (p=0.03), and a 4.7% decrease in mean V˙O2max from 4.83±0.29 to 4.61±0.41 L/min as well as a 2.8% increase of body mass from 75.1±6.4 to 77.1±6.1 kg and a 28% increase in skinfold total from 43.9±14.2 to 55.1±14.0 mm. Individual decreases in Hbmass following detraining would need to be considered if using Hbmass for anti-doping purposes.
Keywords: erythropoesis; training; anti doping